Can Sacropelvic Fixation Improve Outcome of Long-Segment Lumbar Spine Fusion in Patients with Degenerative Lumbar Spine Disease? - Shamel Elgawhary, MD. (Egyptian Spine Association, 2020)
Background Data: Posterior spinal fusion has been more and more used for management of degenerative disorders of the lumbosacral spine. Long-segment fixation of three or more motion segments extending down to the sacrum has been associated with loosening or failure of S1 screws. Purpose: Comparison between fixations extending to S1 and those to S2 (S2-alar-iliac screws) with sacropelvic fixation in the management of multilevel lumbar spinal canal stenosis. Study Design: Prospective controlled cohort study. Patients and Methods: We recruited 45 patients suffering from lumbar spinal canal stenosis of 3 or more levels including 16 revision cases in the whole group. In 23 patients, posterior lumbar fusion extended to S1 and in 22 fixations extended to S2. Pre- and postoperative clinical evaluation included Visual Analogue Scale (VAS) for back pain and Oswestry Disability Index (ODI). Preoperative radiological evaluation included plain X-ray and MRI. Postoperative clinical evaluation included VAS and ODI and radiological evaluation included X-ray and CT. The mean follow-up duration was 14.1±1.7 months (range, 12–24) in S1 group and 14.3±1.9 months (range, 12–24) in S2 group. Results: The mean VAS improved from 8.1±0.8 to 4.9±0.9 in S1 group and from 7.7±1.2 to 1.95±0.79 in S2 group. The mean ODI improved from 77±10.5 and 76.8±10.9 to 45.9±7.3 and 29.5±8.4 in S1 and S2 groups, respectively. Two dural tears were repaired intraoperatively with no postoperative consequences. Seven cases in S1 group had loosening of S1 screw that was evident at 6-month follow-up. Conclusion: Sacropelvic fixation in the form of S2-alar-iliac screws provides a significantly more rigid construct, decreasing the incidence of loosening of S1 screws and improving the overall outcome in patients treated with long lumbar fusion. (2019ESJ199)